2021
DOI: 10.3390/ani12010022
|View full text |Cite
|
Sign up to set email alerts
|

Saliva and Blood Cortisol Measurement in Bottlenose Dolphins (Tursiops truncatus): Methodology, Application, and Limitations

Abstract: A central task of zoos and aquaria is the frequent and accurate assessment of their animals’ welfare. Recently, important steps have been made, such as the introduction of animal welfare evaluation tools and welfare decision trees. To determine animal welfare, it is not only important to collect life history data, such as longevity and reproductive success, but also for experienced observers or caretakers to conduct behavioral observations on a regular basis to assess animals’ emotional state. To physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…Stress can depress the immune system, which increases the amount of circulating heterophils 41 . Therefore, MGD contributed to providing fish with more welfare due to its comfortable movement and free swimming in the water, which helped reduce their stress hormones and decreased the H/L ratio 15 . The MGD contributed to improving welfare and promoting a healthy H/L ratio, for example, by providing fish with a clean, comfortable environment and feeding animals a healthy diet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress can depress the immune system, which increases the amount of circulating heterophils 41 . Therefore, MGD contributed to providing fish with more welfare due to its comfortable movement and free swimming in the water, which helped reduce their stress hormones and decreased the H/L ratio 15 . The MGD contributed to improving welfare and promoting a healthy H/L ratio, for example, by providing fish with a clean, comfortable environment and feeding animals a healthy diet.…”
Section: Resultsmentioning
confidence: 99%
“…One study published in the journal Animals in 2022 found that fish raised in rectangular ponds with rounded corners had lower blood cortisol levels than fish raised in square ponds. Cortisol is a stress hormone, so this suggests that the rectangular ponds with rounded corners were less stressful for the fish 15 . The fish raised in circular ponds had higher levels of some blood proteins, including albumin and immunoglobulin G, than fish raised in rectangular ponds.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the goal of any investigation developed in those facilities might be conducted along with the enhancement of innovative approaches and/or the improvement of sampling techniques to assess their well-being through minimally-or noninvasive methods, usually aiming to avoid long-lasting manipulations of animals (Zemanova, 2020;Schilling et al, 2022). Hence, different methods that minimize impact while sampling marine mammals in managed care have been reported, including the use of exhaled breath condensate to examine respiratory-associated microbial microorganisms (Lima et al, 2012), rubberized scrapers to obtain sloughed skin to further determine skin cortisol concentrations (Bechshoft et al, 2015), or swabs to collect saliva (Rickert et al, 2022), among others.…”
Section: Introductionmentioning
confidence: 99%
“…For most biotypes, cortisol levels are at their highest in the morning, which can reflect the function of the adrenal cortex, usually around 9 a.m. [ 15 ]. Saliva has been proven to have high correlation values to cortisol levels in blood with a non-invasive in situ collection method, so it is more lucrative for cortisol determination compared with blood [ 16 , 17 ]. In clinical practice, about 80% of the cortisol in the blood is combined with cortieosteroid-binding globulin (CBG), and the rest is in a free state [ 18 ].…”
Section: Introductionmentioning
confidence: 99%